MelRisk: Using neutrophil-to-lymphocyte ratio to improve risk prediction models for metastatic cutaneous melanoma in the sentinel lymph node. Issue 5 (May 2022) - Wade, Ryckie G.; Bailey, Samuel; Robinson, Alyss V.; Lo, Michelle C.I.; Peach, Howard; Moncrieff, Marc D.S.; Martin, James
Summary: Background: Identifying metastatic melanoma in the sentinel lymph node (SLN) is important because 80% of SLN biopsies are negative and 11% of patients develop complications. The neutrophil-to-lymphocyte ratio (NLR), a biomarker of micrometastatic disease, could improve prediction models for SLN status. We externally validated existing models and developed 'MelRisk' prognostic score to better predict SLN metastasis. Methods: The models were externally validated using data from a multicenter cohort study of 1, 251 adults. Additionally, we developed and internally validated a new prognostic score `MelRisk', using candidate predictors derived from the extant literature. Results: The Karakousis model had a C-statistic of 0.58 (95% CI, 0.54–0.62). The Sondak model had a C-statistic of 0.57 (95% CI 0.53–0.61). The MIA model had a C-statistic of 0.60 (95% CI. 0.56–0.64). Our 'MelRisk' model (which used Breslow thickness, ulceration, age, anatomical site, and the NLR) showed an adjusted C-statistic of 0.63 (95% CI, 0.56–0.64). Conclusion: Our prediction tool is freely available in the Google Play Store and Apple App Store, and we invite colleagues to externally validate its performance .